Twin pregnancy with one fetus and one complete mole: a case report = Zwillingsschwangerschaft aus einem Fetus und einer kompletten Mole : ein Fallbericht - Freis, Alexander; Elsässer, Michael; Sohn, Christof; Fluhr, Herbert (Geburtshilfe und Frauenheilkunde, 2016)
Twin pregnancy consisting of one fetus and one complete mole (CMCF, complete hydatidiform mole and a coexistent fetus) is an obstetric rarity with an incidence of 1/22 000 to 1/100 000 pregnancies. Associated risks include prematurity, intrauterine death, vaginal bleeding, preeclampsia, hyperthyroidism, theca lutein cysts, uterine rupture and the development of malignant neoplasia in the form of a trophoblastic tumour (GTD, persistent gestational trophoblastic disease), which is thought to be the most common complication. We report the case of a 33-year-old patient diagnosed with CMCF in the 15th week of pregnancy. After comprehensive counselling the patient chose to proceed with her pregnancy under close observation and prophylactic fetal lung maturation. We were able to extend the pregnancy to 32 weeks gestation when heavy vaginal bleeding forced a decision to deliver by caesarean section.